Turbulence Amplification with Incidence at the Leading Edge of a Compressor Cascade - Garth V. Hobson; Bryce E. Wakefield; William B. Roberts (International Journal of Rotating Machinery)
Detailed measurements, with a two-component laser-Doppler velocimeter and a thermal anemometer were made near the suction surface leading edge of controlled-diffusion airfoils in cascade. The Reynolds number was near 700,000, Mach number equal to 0.25, and freestream turbulence was at 1.5% ahead of the cascade.